Implementation and Effectiveness of Project-Based Learning in the Japanese-Indonesian Translation Course - Dwi Astartia, Dina; Rochim, Julita Fahrul; Hapsari, Intan; Darrienda, Aldilah Alifany; Fatin, Jihan Salsa Biela (Chi e Journal of Japanese Learning and Teaching, 2024)
This study aims to describe two primary issues in the following case study: (1) how Project-Based Learning (PjBL) is applied, and (2) whether students can implement “proactive learning,” “interactive learning,” and “authentic learning” through PjBL. Based on the findings, we also explore an outline and framework for PjBL, specifically in a Japanese Translation course. The study examines the effectiveness and implementation of PjBL by analyzing observations and interviews with students during the project “Translation and Japanese-Indonesian Subtitling for Occupational Safety Training for Indonesian Workers in Japan's Manufacturing Industry.”The results indicate that PjBL was conducted in five steps: (1) connecting to the problem, (2) setting the structure, (3) revisiting the problem, (4) producing the product, and (5) evaluation. We conclude that by following these steps, students effectively implemented “proactive learning,” “interactive learning,” and “authentic learning.”.